2022
DOI: 10.1039/d2fo00680d
|View full text |Cite
|
Sign up to set email alerts
|

Mycelium polysaccharides of Macrolepiota procera alleviate reproductive impairments induced by nonylphenol

Abstract: Mycelium polysaccharides of Macrolepiota procera (MMP) had positive role in amelioration of NP-induced reproductive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…These complexes combine the beneficial effects of both PSs and proteins. Furthermore, it has been found that MP mycelium PSs show protective activity on experimental male mice against nonylphenol toxicity via alleviating the oxidative stress, apoptosis, autophagy, and inflammatory responses in testicular cells [ 35 ]. Water-extractable PSs from the wild parasol mushroom have exhibited antioxidant and prebiotic activities in vitro, but their structure and immunomodulatory effects have not been elucidated [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…These complexes combine the beneficial effects of both PSs and proteins. Furthermore, it has been found that MP mycelium PSs show protective activity on experimental male mice against nonylphenol toxicity via alleviating the oxidative stress, apoptosis, autophagy, and inflammatory responses in testicular cells [ 35 ]. Water-extractable PSs from the wild parasol mushroom have exhibited antioxidant and prebiotic activities in vitro, but their structure and immunomodulatory effects have not been elucidated [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The approximate MW of the polysaccharide extract from M. procera (from China) obtained by the ethanol precipitation from hot water extract method was expressed as 7.71 × 10 5 Da . Qu et al calculated the approximate MW of Hygrophorus lucorum polysaccharide extract (obtained by the ethanol precipitation from the hot water extract method) as 20.4 kDa .…”
Section: Resultsmentioning
confidence: 99%
“… 23 The approximate MW of the polysaccharide extract from M. procera (from China) obtained by the ethanol precipitation from hot water extract method was expressed as 7.71 × 10 5 Da. 38 Qu et al calculated the approximate MW of Hygrophorus lucorum polysaccharide extract (obtained by the ethanol precipitation from the hot water extract method) as 20.4 kDa. 39 The main reason for this discrepancy in the approximate MWs of polysaccharide extracts between the results in the literature and our research may be due to the differences in mushroom species and extraction methods or applications.…”
Section: Resultsmentioning
confidence: 99%
“…At least 50 seminiferous tubules were analyzed in each mouse in order to obtain an effective, accurate, and representative evaluation. 25,29…”
Section: Histopathological Analysesmentioning
confidence: 99%